Problematika atas Putusan MK terhadap Batasan Umur Capres - Cawapres ( Pasal 169 huruf q Undang-Undang Nomor 7 Tahun 2017) - Agus, Rizka Bintang; Satryo Pringgo Sejati; Ahmad Burhan Hakim (Program Studi Hukum Tata Negara dan diterbitkan oleh Program Studi Hukum Tata Negara dan Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Sunan Drajat Lamongan, 2024)
The purpose of the Constitutional Court is to protect the Constitution so that it is in accordance with the principles of legal constitutionality. the public was shocked by the decision of the Constitutional Court (MK) which was considered controversial. This article uses a descriptive qualitative method using the library research analysis method. The author will conduct research on books, journals, magazines, newspapers both offline and online. In its decision, the Constitutional Court decided that regional heads under the age of 40 can nominate themselves as candidates for president or vice president, if they have previously served or are currently carrying out duties as regional heads. The impact of the Constitutional Court's decision to grant the addition of the narrative to Article 169 letter q of Law Number 7 of 2017 does not only have an impact on agitation and the political map ahead of the 2024 election. However, the impact could be even more dire. Not only among contestants in the 2024 election, heated escalation is also occurring in society. What state institutions can still be trusted, the Constitutional Court has become a tool of power, corruption is rampant in ministries, the Corruption Eradication Commission (KPK) should supervise the implementation of the Corruption Law. in fact, it turned out to have become a